An introduction to business accounting for managers - Hartley, W. C. F. (Pergamon international library of science, technology, engineering, and social studies., 1980)
An Introduction to Business Accounting for Managers, Third Edition reviews developments in the business accounting arena, including the crystallization of accounting thought on how to deal with escalating rates of inflation, culminating in the proposals for Current Cost Accounting; the acute cash crisis, itself an offshoot of inflation, faced by many companies in the mid-1970s leading to a greater need for awareness and control of cash flow; the specter of several major company collapses and scandals leading to a growing demand for accounting standards; and the growing use of value added within accounting and reporting systems.